The Slope of the Credit Yield Curve for Speculative‐grade Issuers - Helwege, Jean; Turner, Christopher M. (Journal of Finance, 1999)
Many theoretical bond pricing models predict that the credit yield curve facing risky bond issuers is downward‐sloping. Previous empirical research (Sarig and Warga (1989), Fons (1994)) supports these models. Our study examines sets of bonds issued by the same firm with equal priority in the liability structure, but with different maturities, thus holding credit quality constant. We find, counter to prior research, that risky bonds typically have upward‐sloping credit yield curves. Moreover, when we combine our matched sets of bonds (no longer controlling credit quality), the estimated slope is negative, indicating a sample selection bias problem associated with maturity.